The Relationship Between Knowledge and Family Support with the Quality of Life of Chronic Kidney Failure Patients Undergoing Hemodialysis at Byahangkara Hospital, Level 1, National Police Health Center - Silalahi, Martha Katarina; Hardayati, Anastasia; Muhafilah, Ilah; Suwarningsih; Asmarani, Khansa Nabila (LPPM Universitas Mohammad Husni Thamrin, 2025)
Background: Chronic kidney failure is one of the 12 leading causes of death worldwide. Chronic kidney disease (CKD) is a condition in which kidney function begins to decline progressively over months or even years. Chronic kidney disease (CKD) is closely related to degenerative processes resulting from damage to the body's organs. Degenerative diseases associated with an increased incidence of CKD include diabetes mellitus, hypertension, and coronary heart disease. Chronic kidney disease (CKD) is a progressive and irreversible renal dysfunction that causes uremia, requiring hemodialysis to maintain life. This is related to knowledge and family support in improving the quality of life of chronic kidney disease patients undergoing hemodialysis. Objective: To determine the relationship between knowledge and family support in chronic kidney disease patients undergoing hemodialysis at Bhayangkara Hospital, Class I, Indonesian National Police Health Center. Method: This study was quantitative with a cross-sectional approach. The sample size was 40 people, with a total sampling technique, and the data were tested using chi-square. Results: The results showed a relationship between knowledge and family support with quality of life with a p-value of 0.012 and a p-value of 0.002. Conclusion: There is a relationship between knowledge and family support with quality of life in chronic kidney disease patients undergoing hemodialysis at Bhayangkara Hospital, Class I, Indonesian National Police Health Center.